Acute Otitis Media in an Extremely Preterm Infant - Janwadkar, Aashika; Louis, Shirley; Nemerofsky, Sheri L. (American Journal of Perinatology Reports, 2021)
There are a limited number of documented cases of acute otitis media (AOM) in preterm infants while hospitalized in the neonatal intensive care unit (NICU). We present a case of a former 26 weeks old infant who at 29 weeks, 6 days postmenstrual age presented with acute signs and symptoms of systemic sepsis subsequently found to be secondary to AOM with purulent ear drainage. The patient received a septic evaluation, including urine, blood, and cerebrospinal fluid studies. Treatment included intravenous antibiotics with full resolution of symptoms. AOM in extreme preterm infants is multifactorial, with leading causes that include prematurity, the use of oropharyngeal and nasogastric tube placement and endotracheal intubation, eustachian tube dysfunction, and a distinct immune response. To our knowledge, there is not another published case of AOM of a preterm baby while in the NICU.
Keywords: acute otitis media; preterm; NICU; otorrhea